More evening preference is positively associated with systemic inflammation in prediabetes and type 2 diabetes patients. Issue 1 (December 2018) - Nimitphong, Hataikarn; Mahattanapreut, Apichana; Chailurkit, La-or; Saetung, Sunee; Siwasaranond, Nantaporn; Sumritsopak, Rungtip; Anothaisintawee, Thunyarat; Thakkinstian, Ammarin; Dugas, Lara; Layden, Brian; Reutrakul, Sirimon
Abstract Currently it is not known whether morningness-eveningness preference in non-night shift working population is associated with systemic inflammation. This study investigated the relationship between morningness-eveningness and systemic inflammation, as measured by high-sensitivity C-reactive protein (hs-CRP) in 163 non-night shift working patients with abnormal glucose tolerance (86 type 2 diabetes and 77 prediabetes). Morningness-eveningness was assessed by Composite Scale of Morningness, and participants were screened for Obstructive sleep apnea (OSA). Sleep duration, efficiency, and variability were obtained using actigraphy, and depressive symptoms and dietary patterns were also captured. Participants' mean age was 54.7 ± 10.4 years and median hs-CRP was 1.39 (interquartile range 0.82, 3.33) mg/L. More evening preference was significantly associated with higher natural log transformed (ln) hs-CRP (B = −0.051, p = 0.001). Diabetes status, glycemic control, OSA severity, sleep duration, caloric consumption and timing were not related to hs-CRP. After adjusting for age, sex, body mass index, depressive symptoms, sleep efficiency, sleep variability, percentage of daily caloric intake from protein, and statin use, more evening preference was independently associated with higher ln hs-CRP (B = −0.032, p = 0.014). In summary, in non-night shift working patients with abnormal glucose tolerance, more evening preference was independently associated with higher systemic inflammation. This finding underscore the importance of circadian regulation on cardiovascular health.